The Importance of ethics in e-commerce company and employee responsibilities. - Bishnu Barman; Dr C Neela Devi (Revista Electronica de Veterinaria, 2026)
The foundation of social, organizational, and political databases pertaining to the internet is ethics. The study of principles that people and organizations can use to decide what is right and wrong is known as ethics. It is makes the assumption that people are moral beings with free will who are capable to making decisions. Building trust, guaranteeing ethical corporate practice, and defending consumer rights all. Depend on ethics in e-commerce. In addition to following the law and moral principles, businesses have an obligation to maintain openness, data security and reasonable prices. Employees are required to uphold honesty, protect the privacy of. customers and stop fraud. Long term company success, consumer loyalty and brand reputation are a" improved by ethical e-commerce methods. This article examines the moral obligations that businesses and workers have to uphold an honest reliable internet marketplace.